Enhanced precipitation strengthening effect and ductility of Mg-Gd-Y-Zn-Zr alloy by short-time solid solution prior to aging - Xu Wang; Ming Li; ShengXiong Tang; Yuanchun Huang; Yu Liu; Changqing Huang (Journal of Materials Research and Technology)
Enhanced precipitation strengthening effect and ductility of Mg-9.8Gd-3.6Y-2.2Zn-0.4Zr alloy are achieved by short-time solution treatment prior to aging, and the effects of short-time solution on microstructure differences, strengthening contribution and fracture behavior are analyzed. The IF (initial-forged state) and PA (peak-aged state) samples exhibit the similar microstructure, with numerous fragmented lamellar LPSO phase distributed within the matrix and relatively uniform small grains (∼9 μm). The significant increase in grain size of SS (solid solution state) and SSPA (solid solution + peak-aged state) samples (23.1 μm and 27.0 μm) is related to the lack of “pinning effect” caused by the dissolution of fragmented lamellar LPSO phase, meanwhile, the fully excited static recrystallization during the solution process results in high recrystallization fraction (above 95%) for both the two samples. The σgb (grain boundary strengthening) and σss (solid solution strengthening) contribute more than 70% in both IF and SS samples, while σgb and σpp (precipitation strengthening) dominate in the PA and SSPA samples. The stronger precipitation strengthening effect and age-hardening response of SSPA sample are derived from the more and denser β′ precipitates within the matrix. The deformation mechanism of PA sample is the grain boundaries sliding of fine-sized grains and the slip of blocky LPSO phase, the microcracks are mainly concentrated at the grain boundaries, the blocky LPSO phase and its interface with matrix. As a comparison, the tensile deformation mechanism of SSPA sample is sufficient intragranular slip, the microcracks are mainly concentrated at the blocky LPSO phase and extend into the matrix, and finally forming large-sized cracks and deep fracture holes, which enhances the ductility. This paper may provide new ideas for the aging process design of wrought Mg-Gd-Y-Zn-Zr alloys.